Single-hole Ag / Ag2S reference electrode for chloride molten salt

By using Ag2S plating and micron-scale single-hole quartz electrode shell in chloride molten salt, the potential instability and silver ion leakage of Ag/AgCl reference electrode are solved, and Ag/ in high-temperature chloride molten salt is realized The stability and consistency of the Ag+ reference electrode simplifies the preparation process and is suitable for electrochemical testing of molten chloride salts at 300-800°C.

CN119147602APending Publication Date: 2024-12-17INST OF HIGH ENERGY PHYSICS CHINESE ACAD OF SCI

Patent Information

Application Number
CN202410995443.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-24
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The Ag/AgCl reference electrode in the existing chloride molten salts has problems with potential instability and silver ion leakage. The preparation process is cumbersome and has poor consistency, which limits its application in high-temperature chloride molten salts.

Method used

Using Ag2S plating as silver ion donor, micron-scale single holes are designed at the bottom of the quartz electrode shell, combined with dense Ag2S plating and double helix silver wire structure, chemical regulation of silver ion activity and stability of the diaphragm material are achieved, reducing the Silver ion leakage improves the stability and consistency of the electrode.

Benefits of technology

The stability and consistency of Ag/Ag+ reference electrode in high-temperature chloride molten salt is achieved, the preparation process is simplified, and the reproducibility and application performance of the electrode are improved. It is suitable for chloride molten salt electricity at 300-800℃. Chemical testing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119147602A_ABST
    Figure CN119147602A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of molten salt electrochemical electrode materials, in particular to a single-hole Ag / Ag2S reference electrode for chloride molten salt. The reference electrode structurally comprises an electrode shell made of a quartz material; a micron-sized single hole is formed in the bottom of the electrode shell; a reference inner solution is contained in the electrode shell; a spiral silver wire plated with an Ag2S plating layer is arranged in the electrode shell, the spiral silver wire is partially immersed in the reference inner liquid, and the tail end of the part, not in contact with the reference inner liquid, of the spiral silver wire is connected with a metal lead. The Ag / Ag < + > reference electrode for the chloride molten salt system is high in stability, good in reproducibility, high in consistency, capable of being repeatedly used, rapid in response and easy to prepare, is suitable for high-temperature chloride molten salt, the applicable temperature is 300-800 DEG C, and molten salt electrochemical testing and research can be stably and reliably carried out.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of molten salt electrochemical electrode materials, and in particular to a single-hole Ag / Ag2S reference electrode for chloride molten salt. Background Art

[0002] When conducting precise electrochemical measurement and control and electrochemical research, reference electrodes are essential and are one of the core foundations in the field of electrochemistry. High-temperature chloride molten salts are widely used in spent fuel reprocessing in nuclear energy systems and in metal metallurgy. However, due to the high temperature, high corrosiveness, and complex molten salt systems and environments of chloride molten salts, there is currently no universal reference electrode.

[0003] In chloride molten salts, the reference electrodes mainly used in academia are chlorine reference electrodes (Cl - / Cl2), Ag / AgCl reference electrode, Pb / PbCl2 reference electrode, Pt / PtCl2 reference electrode, Mg / MgCl2 reference electrode and alloy reference electrode (Bi-Li), as well as a series of quasi-reference electrodes used directly in the melt, such as Pt, W, Mo, etc.

[0004] In practical applications, the use of chlorine reference electrodes is limited due to their complex structure, difficult preparation, and strong oxidizing properties of chlorine. In recent years, they have been mainly used for potential correction of secondary reference electrodes. In contrast, alloy electrodes and quasi-reference electrodes are simple to prepare and are mainly used for electrolysis and pre-testing in chloride molten salts. However, due to their unclear potential mechanism and the influence of composition and concentration, it is difficult to provide test data with thermodynamic significance. Metal / metal ion reference electrodes have clear reaction pairs, and test data with thermodynamic significance can be obtained through potential correction. They are widely used in the study of electrochemical mechanisms of chloride molten salts. Among them, the Ag / AgCl reference electrode has excellent reversibility in chloride molten salts, a large exchange current density, and a relatively low price. Therefore, it is widely used and regarded as the most promising chloride molten salt electrode.

[0005] The existing Ag / AgCl reference electrode still has problems of potential instability and silver ion leakage. It has been confirmed that the traditional mullite as a diaphragm material cannot effectively prevent the exchange of molten salt substances inside and outside the reference. In view of the low melting point of AgCl, it exists in a liquid state in the conventional 500 °C LiCl-KCl molten salt, which makes the concentration of silver ions lack chemical equilibrium, and its leakage will directly affect the stability and accuracy of the reference electrode. Therefore, it is necessary to further research and develop new silver ion donors or improve the diaphragm design to solve the stability and leakage problems of the Ag / AgCl reference electrode, thereby improving its application performance in chloride molten salts.

[0006] In the prior art, CN117347451A proposes an Ag / AgCl reference electrode for a chloride molten salt system and a preparation method thereof. 5+ Doping mullite improves the membrane resistance and ion transport performance of the diaphragm material, thereby improving the design and improving the stability and reproducibility of the reference electrode. However, this improved diaphragm material needs to be polished into a 0.05~0.3 mm thick film at its bottom, and then undergo a pre-activation time of up to 20~500 hours. This preparation process is cumbersome and time-consuming, which may limit its promotion in practical applications. At the same time, there is a problem of consistency in the manually polished film, which also needs to be further solved to improve the consistency of the prepared reference. CN109752427A proposes an alloy reference electrode for a high-temperature molten salt system, and a boron nitride outer tube is designed, with micropores with an aperture of 0.4~1.0 mm on the tube wall for connecting the reference electrode to the test system. However, due to the unclear equilibrium pair of the alloy reference electrode and the unclear potential stabilization mechanism, it is impossible to perform an effective electrochemical mechanism analysis of the equilibrium reaction in the reference. At the same time, the preparation process needs to be smelted for 6 to 8 hours to obtain the alloy for preparing the reference electrode, which is not only time-consuming but also requires high equipment. CN2685874Y proposes a high-temperature fully sealed reference electrode, in which the Ag / AgCl reference electrode uses quartz as the diaphragm material and the bottom wall thickness is 0.5 mm. The reference salt uses LiCl-KCl-NaCl, and the ion conduction inside and outside the reference is achieved through sodium ion conduction. However, its scope of application is limited by the sodium ion concentration, and the sodium ion concentration in the melt needs to be calibrated, which has the inherent defects of the ion conductive membrane salt bridge.

[0007] Based on the current research and application of reference electrodes for chloride molten salts, it can be seen that various designs have different problems, such as complex production, long time consumption, high equipment requirements, poor consistency, possible system contamination, unclear mechanism, and system limitations. These problems will affect the performance, stability and reliability of the reference electrode, thus limiting the Ag / Ag + Application and promotion of reference electrodes. Summary of the invention

[0008] In order to solve the above technical problems, the present invention provides a Ag / Ag catalyst for chloride molten salt system which has strong stability, good reproducibility, high consistency, reusability, fast response and is easy to prepare. + A reference electrode, wherein the structure of the reference electrode comprises: An electrode shell (4) made of quartz material; a micrometer-sized single hole (7) is arranged at the bottom of the electrode shell (4); a reference internal solution (6) is contained in the electrode shell (4); a spiral silver wire (5) plated with an Ag2S coating is arranged in the electrode shell (4), a portion of the spiral silver wire (5) is immersed in the reference internal solution (6), and a metal lead (3) is connected to the end of the spiral silver wire (5) that is not in contact with the reference internal solution.

[0009] Current research focuses on the diaphragm material as the key to improving the stability and reproducibility of the reference electrode in the molten salt system, but ignores the more fundamental factor, namely the chemical balance of silver ion activity. + The reference electrode uses AgCl as the silver ion donor, and in high-temperature molten salt (above 450°C), AgCl is completely dissolved, and the activity of silver ions is mainly regulated by the amount added. For non-selective conductive diaphragm materials, such as porous materials such as mullite, corundum, and boron nitride, during the conductive process, the silver ions in the reference internal solution will slowly seep into the test melt, causing the Ag / AgCl reference potential to change and the stability to decrease.

[0010] Ion-selective diaphragm materials, such as Pyrex glass and quartz glass, have advantages in some aspects, but also have some problems, such as Pyrex glass is easy to break in high-temperature melts, quartz glass has too low conductivity below 700°C, and ion transmission performance is affected by sodium ion concentration. Therefore, when using AgCl as a silver ion donor, the design requirements for the diaphragm are constantly increasing, and no material can fully meet the requirements.

[0011] The present invention forms a dissolution equilibrium in a reference internal solution by using an Ag2S coating as a silver ion donor, and realizes the regulation of the activity of silver ions by the solubility of Ag2S. Since the solubility of Ag2S is a constant in a chloride melt at a specific temperature and pressure, and the Ag2S coating can play a role in corrosion protection, avoiding the presence of other sources of silver ions in the system, it will not be disturbed by the ion transmission of the internal and external systems during the test. Therefore, for the design of the diaphragm material, there is no need to consider the influence of silver ion leakage on the reference potential, and only the pollution problem of the test system and the effectiveness and stability of the ion transport of the diaphragm need to be concerned, which reduces the burden of the diaphragm material design.

[0012] In addition, the present invention takes into account the effectiveness of the internal and external conduction of the reference electrode, and selects quartz material as the electrode shell, which has excellent high temperature resistance. In order to overcome the problem of low conductivity and sodium ion concentration dependence of quartz, the bottom adopts a micron-level single-hole design so that the internal and external systems are directly connected and are not affected by the conductivity of quartz and the sodium ion concentration. And compared to porous materials, this design is easier to ensure the consistency of the diaphragm, no pre-activation is required, and it is not affected by the molten salt corrosion on the pore distribution during long-term testing. At the same time, due to the extremely low solubility of Ag2S, the volume of the reference internal solution is relatively small, and it will not have a significant impact on the test system, so it can meet the use requirements of the reference electrode in the current chloride molten salt system.

[0013] Preferably, the pore size of the micrometer-sized single hole (7) ranges from 1 to 30 micrometers.

[0014] The smaller the aperture of the micrometer-scale single hole (7) is under processable conditions, the better.

[0015] Preferably, the Ag2S coating on the surface of the spiral silver wire (5) not immersed in the reference internal solution (6) is 4 to 5 cm higher than the liquid level of the reference internal solution (6).

[0016] Preferably, the electrode shell (4) is uniform and does not contain any porous structure.

[0017] In the specific implementation process, the reference internal solution (6) can be adjusted according to the actual test system to keep it consistent with the chloride molten salt system of the test melt. When the pore size is small enough, the corresponding molten sulfide can be used for supersaturation design. Taking the 45wt.% LiCl-55wt.%KCl molten salt test system as an example, the reference internal solution is also 45wt.%LiCl-55wt.%KCl.

[0018] Preferably, the raw material of the reference internal solution (6) is chloride molten salt; preferably 45wt.% LiCl and 55wt.% KCl chloride molten salt.

[0019] Preferably, the metal lead wire (3) is a silver wire or a different metal wire other than silver wire.

[0020] The heterogeneous metal wire is a metal wire with good electrical conductivity and plays a role in electron conduction.

[0021] Preferably, the structure of the reference electrode further comprises: A plug (1) for fixing the spiral silver wire (5); The adhesive tape (2) is wrapped around the connection between the stopcock (1) and the electrode housing (4) and is used to encapsulate the reference electrode.

[0022] In the specific implementation process, the stopcock is a high temperature resistant stopcock, including but not limited to a high temperature resistant inorganic rubber sealing plug or other high temperature resistant piston, preferably a quartz stopcock.

[0023] In the specific implementation process, the tape is a high temperature resistant tape.

[0024] Preferably, the reference electrode is assembled in an inert gas environment, and the gas inside the reference electrode after sealing is an inert gas; preferably, the inert gas is Ar gas.

[0025] During the specific implementation process, the assembly, storage or use can be carried out in a glove box with an inert gas environment.

[0026] Preferably, the Ag2S coating is prepared by in-situ oxidation deposition in a supersaturated sodium sulfide aqueous solution.

[0027] The Ag2S coating prepared by in-situ oxidation deposition in a supersaturated sodium sulfide aqueous solution has a dense structure and plays a better role in corrosion protection as a silver wire protective layer, avoiding the presence of other silver ion sources in the system.

[0028] Preferably, the spiral silver wire (5) is a double spiral silver wire.

[0029] Preferably, the diameter of the silver wire is 0.5-2 mm.

[0030] Preferably, the outer diameter of the electrode shell (4) is 5-10 mm, and the wall thickness is 1-3 mm. The tube length can be adjusted according to the use environment.

[0031] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides an Ag / Ag catalyst for chloride molten salt system which has strong stability, good reproducibility, high consistency, reusability, rapid response and is easy to prepare. + The reference electrode is suitable for high-temperature chloride molten salts with an applicable temperature of 300-800°C. It can stably and reliably carry out molten salt electrochemical testing and research. The specific advantages are: 1. High electrode potential stability. The present invention realizes chemical regulation of silver ion activity by introducing the dissolution equilibrium of Ag2S. Through the dense Ag2S coating, corrosion protection of silver wire is achieved at the same time, ensuring that only Ag / Ag exists in the electrode reaction. + A single reversible reaction keeps the activity of silver ions constant. The micrometer-level single hole at the bottom of the quartz tube is designed to make the reference electrode conductive inside and outside, and is not affected by the conductivity and transmission performance of the diaphragm material, reducing the interference of membrane resistance and interface potential on the apparent electrical signal of the reference electrode. In addition, the double helix structure of the silver wire is designed to increase the surface area involved in the electrode reaction and improve the Ag / Ag ratio of the reference electrode.+ The weight of the electric couple reaction in the apparent electrical signal. These measures together improve the stability of the electrode.

[0032] 2. The consistency of the reference electrode is high. The present invention uses quartz as the reference electrode shell, and the bottom is punched by laser to obtain a single micron-sized hole. The wall thickness of the quartz tube is 1-3 mm, and no ion conduction is performed, and the micron pore size is used as a conduction path. Compared with porous materials, the consistency of the electrode shell and the ion transmission path is higher. Porous materials use their pores as the path of ion conduction, and their pore structure is complex. The size and distribution of the pore structure are affected by the sintering temperature, sintering components and corrosion, resulting in poor consistency between materials. Changes in the pore structure will affect the size of the apparent electrical signal, thereby reducing the consistency of the reference electrode prepared by the porous material. The preparation process of single-pore quartz is more controllable, and the ion transmission path is single, so the consistency of the reference electrode prepared by the single-pore quartz tube is better. It should be noted that the use of the single-pore quartz shell must rely on the Ag / Ag2S reference electrode. The traditional Ag / AgCl reference electrode cannot achieve the control of silver ion activity through chemical equilibrium. The use of a single-hole electrode may accelerate the leakage of silver ions, causing changes in the activity of silver ions in the reference, thereby affecting the potential stability of the reference electrode. Therefore, when designing and applying a single-hole quartz shell reference electrode, it is necessary to consider the method of regulating the activity of silver ions to ensure the potential stability of the reference electrode.

[0033] 3. The preparation process and electrode structure are simple. The preparation process of the single-hole Ag / Ag2S reference electrode of the present invention is simple and does not require long-term activation. The diaphragm does not need to be polished or pre-activated and turned on. The reference salt does not need to be pre-mixed and ground with the addition of AgCl. Ag2S is deposited by electrochemical in-situ deposition, and the electrolysis time is only five minutes. In addition, the structure of the single-hole Ag / Ag2S reference electrode is simple, which is convenient for production, preparation and promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 It is a structural schematic diagram of a single-hole Ag / Ag2S reference electrode provided by the present invention; wherein, 1: high-temperature resistant stopper; 2: high-temperature resistant tape; 3: metal lead; 4: electrode shell; 5: double-helix silver wire plated with Ag2S coating; 6: reference internal solution; 7: micron-level single hole.

[0035] Figure 2 It is the result of stability test.

[0036] Figure 3 It is the consistency test result. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] If no specific techniques or conditions are specified in the examples, all are carried out according to conventional methods or the techniques or conditions described in the literature in the field, or according to the product instructions. If no manufacturer is specified for the reagents and instruments used, all are conventional products that can be purchased through regular channels.

[0039] Example

[0040] This embodiment provides a single-hole Ag / Ag2S reference electrode for a chloride molten salt system, such as Figure 1 As shown, the structure includes: An electrode shell 4 made of quartz material has an outer diameter of 7 mm, an inner diameter of 5 mm and a length of 290 mm; a single hole 7 with an aperture of 30 microns is arranged at the bottom of the electrode shell 4; a reference internal solution 6 is contained in the electrode shell 4; the raw materials of the reference internal solution 6 are 45wt.% LiCl and 55wt.% KCl chloride molten salt; a double helix silver wire 5 (the diameter of a single silver wire is 0.5 mm) coated with Ag2S is arranged in the electrode shell 4, and a part of the double helix silver wire 5 is immersed in the reference internal solution 6, and the Ag2S coating on the surface of the double helix silver wire 5 not immersed in the reference internal solution 6 is 4-5 cm higher than the liquid level of the reference internal solution 6; a metal lead 3 is connected to the end of the part of the double helix silver wire 5 not in contact with the reference internal solution, and the metal lead 3 is a silver wire with a diameter of 0.5 mm; a high temperature resistant plug 1 is used to fix the double helix silver wire 5; a high temperature resistant tape 2 is wrapped around the connection between the high temperature resistant plug 1 and the electrode shell 4, and is used to encapsulate the reference electrode; The preparation method of the reference electrode is as follows: (1) Preparation of Ag2S coating (normal temperature and pressure, atmospheric atmosphere operation): Grind the silver wire with fine sandpaper, then soak it in hydrochloric acid for 3 hours, then wash it with deionized water and ethanol, and finally blow it dry with cold air. Fold the clean and dry silver wire in half, then spirally wind it to obtain a double-helix silver wire. Prepare a supersaturated sodium sulfide aqueous solution as the electrolyte. Build a two-electrode system with the double-helix silver wire as the working electrode and the ordinary silver wire as the counter electrode. Use an electrochemical workstation to apply a 5mA anode current to the working electrode and perform electrolysis for five minutes. Take out the double-helix silver wire to obtain a double-helix silver wire with a dense Ag2S coating on the surface. Wash it with deionized water, blow it dry with cold air and set aside.

[0041] (2) Electrode assembly (operation in an inert gas (Ar) atmosphere glove box): The silver wire containing the Ag2S coating and the single-hole quartz tube are transferred to the glove box. LiCl-KCl eutectic salt (45wt.%:55wt.%) powder is filled in the single-hole quartz tube, and the height of the molten salt is ensured to be 4-5 cm lower than the coating height. Then, the silver wire containing the Ag2S coating is loaded into the single-hole quartz tube, and the single-hole quartz tube is fixed in a crucible containing LiCl-KCl eutectic salt (45wt.%:55wt.%), and then the crucible is placed in a high-temperature electric furnace and the temperature is set to 500 °C. After the LiCl-KCl eutectic salt in the single-hole quartz tube is melted, the silver wire containing the Ag2S coating automatically falls to the bottom of the single-hole quartz tube. The single-hole quartz tube is then lifted up and allowed to cool naturally in the furnace to room temperature before being taken out.

[0042] (3) Packaging: Take out the assembled reference electrode, screw the quartz stopper into the upper opening, and fix it with high-temperature resistant tape to fix the silver wire and package the reference electrode.

[0043] Method of using the reference electrode: Use the above-mentioned single-hole Ag / Ag2S reference electrode as the reference electrode, the W electrode as the working electrode, and the graphite electrode as the auxiliary electrode. Insert the three electrodes into the molten salt respectively, connect the electrochemical workstation, and use the open circuit potential (OCP) to record the potential change. When the potential remains stable within a certain range, it can be considered to be able to be used normally. The single-hole Ag / Ag2S reference electrode prepared in this embodiment has a potential stabilization time of less than 3 hours.

[0044] Test example

[0045] This test example compares the performance of the single-hole Ag / Ag2S reference electrode prepared in the embodiment with that of the traditional mullite Ag / AgCl reference electrode, and the steps are as follows: (1) Weigh 45 g of LiCl and 55 g of KCl salts, mix them evenly, place them in a crucible, dry them in a vacuum oven for 24 hours, and then transfer them to a glove box.

[0046] (2) Weigh 3 grams of SmCl3 powder in a glove box and mix it evenly with the dried molten salt. Then put the mixture into a crucible and place it in a high-temperature electric furnace. Set the target temperature to 500 degrees Celsius and increase the temperature at a rate of 5 degrees Celsius per minute. The single-hole Ag / Ag2S reference electrode prepared in the example and the traditional mullite Ag / AgCl reference electrode (with mullite as the diaphragm material, the reference inner salt is LiCl-KCl eutectic salt and 1 wt% AgCl) are used as reference electrodes to form the above three-electrode system and inserted into the melt. By continuously measuring the open circuit potential (OCP) and cyclic voltammetry (CV), and calculating the Sm 3+ / Sm 2+ The half-wave potential of the reference potential was measured to evaluate the stability of the reference potential.

[0047] The results are as follows Figure 2 As shown, it can be seen that during the long-term test, the half-wave potential deviation of the single-hole Ag / Ag2S reference electrode does not exceed 4 millivolts, and there is no linear change trend, while the half-wave potential deviation of the traditional Ag / AgCl reference electrode reaches 9 millivolts, and presents a linear change trend. Moreover, through mathematical analysis, it can be seen that the single-hole Ag / Ag2S reference electrode shows better stability and reliability during long-term use, and has a longer service life and more stable potential output than the traditional Ag / AgCl reference electrode. Therefore, the single-hole Ag / Ag2S reference electrode of the present invention has excellent stability.

[0048] (3) Three single-hole Ag / Ag2S reference electrodes were prepared in parallel and the consistency was measured. Figure 3 As shown, it can be observed that the potential deviation between the single-hole Ag / Ag2S reference electrodes of the present invention does not exceed 3 millivolts, which can be ignored in the actual use of the reference electrode. This shows that the reference electrode prepared by the present invention has good consistency.

[0049] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A reference electrode, It is characterized in that The structure includes: An electrode shell (4) made of quartz material; a micrometer-level single hole (7) is arranged at the bottom of the electrode shell (4); a reference internal solution (6) is contained in the electrode shell (4); and a Ag-plated 2 A spiral silver wire (5) with an S-plated layer, wherein a portion of the spiral silver wire (5) is immersed in the reference internal solution (6), and a metal lead (3) is connected to the end of the portion of the spiral silver wire (5) that is not in contact with the reference internal solution.

2. The reference electrode according to claim 1, It is characterized in that The pore size of the micrometer-sized single hole (7) ranges from 1 to 30 micrometers.

3. The reference electrode according to claim 1, It is characterized in that Ag on the surface of the spiral silver wire (5) not immersed in the reference internal solution (6) 2 The S coating is 4 to 5 cm higher than the liquid level of the reference internal solution (6).

4. The reference electrode according to claim 1, It is characterized in that The electrode shell (4) is uniform and does not contain any porous structure.

5. The reference electrode according to claim 1, It is characterized in that The raw material of the reference internal solution (6) is chloride molten salt; preferably 45wt.% LiCl and 55wt.% KCl chloride molten salt.

6. The reference electrode according to claim 1, It is characterized in that The metal lead wire (3) is a silver wire or a different metal wire other than silver wire.

7. The reference electrode according to any one of claims 1 to 6, It is characterized in that The structure also includes: A plug (1) for fixing the spiral silver wire (5); The adhesive tape (2) is wrapped around the connection between the stopcock (1) and the electrode housing (4) and is used to encapsulate the reference electrode.

8. The reference electrode according to claim 1, It is characterized in that The reference electrode is assembled in an inert gas environment, and the gas inside the reference electrode after sealing is an inert gas; preferably, the inert gas is Ar gas.

9. The reference electrode according to claim 1, It is characterized in that The Ag 2 The S coating is prepared by in-situ oxidation deposition in a supersaturated sodium sulfide aqueous solution.

10. The reference electrode according to claim 1, It is characterized in that The spiral silver wire (5) is a double spiral silver wire.

Citation Information

Patent Citations

  • Reference electrode

    CN102265147A

  • Reference electrode

    CN102539498A

  • Ni / NiF2 reference electrode used for molten fluoride, and making method thereof

    CN104090004A

  • Silver / silver chloride reference electrode and preparation method thereof

    CN106290503A

  • Alloy reference electrode for high temperature molten salt system and preparation method thereof

    CN109752427A

Cited By

  • Reference electrode for electrochemical measurement of molten salt corrosion

    CN120847201A